2017
DOI: 10.6007/ijarbss/v7-i11/3496
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Purchase Intention of Ready-to-Eat Food among Malaysian Urbanites: A Proposed Framework

Abstract: Changes in life style have brought in profound variations in the purchase intentions among people. This change is even prominent among urban residents who are living a stressful life style and heavily depending on external supplies for their living. In view of this, ready-to-eat food has taken central attention among the urban residents and there are many factors driving such intentions. This conceptual paper will discuss about extrinsic factors that drives purchase intentions among urban residents in Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Low-moisture, ready-to-eat (RTE) meat-based food refers to an animal-derived, cooked and processed product that is typically rich in protein and lipid, and is stabilised by a lowered water activity ( a w < 0.9) to inhibit bacterial growth [1,2,3]. The consumption of meat-based RTE foods has increased, mainly because of a modern and busy lifestyle, which demands for convenience and minimal preparation time [1]. Moreover, its advantages of being readily packed, does not require additional cooking to be safely consumed, energy dense, light-weight (moisture removed) and good stability at varying environments for an extended period of time make it a popular choice among travellers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Low-moisture, ready-to-eat (RTE) meat-based food refers to an animal-derived, cooked and processed product that is typically rich in protein and lipid, and is stabilised by a lowered water activity ( a w < 0.9) to inhibit bacterial growth [1,2,3]. The consumption of meat-based RTE foods has increased, mainly because of a modern and busy lifestyle, which demands for convenience and minimal preparation time [1]. Moreover, its advantages of being readily packed, does not require additional cooking to be safely consumed, energy dense, light-weight (moisture removed) and good stability at varying environments for an extended period of time make it a popular choice among travellers [4].…”
Section: Introductionmentioning
confidence: 99%
“…People found that packaging affected consumers' purchase decisions. Besides, packaging is one of the distinctive factors of a product [3]. Simply defined, packaging is the extrinsic element of a product [4].…”
Section: Impact Of Perceived Packaging On Purchase Intentionmentioning
confidence: 99%
“…Besides, Enni Design consistently gives good packaging to affect customers' purchase intention. Packaging is one of the factors which distinguish a certain product from another competitive product [3]. Packaging is defined as an extrinsic element of a product [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations